Impaired immunoregulatory network of the CD4 T lymphocytes in refractory asthma. Issue 5 (22nd February 2019) - Fernandes, Jamille S.; Araujo, Maria Ilma; de Almeida, Tarcísio V. V. S.; Andrade, Lorena S.; Lopes, Diego M.; de Mello, Luane M.; Carvalho, Edgar M.; Cruz, Álvaro A.; Cardoso, Luciana S.
Summary: Background: The immunopathogenesis of severe asthma has been associated with an inefficient regulatory response. There are a few studies about the CD4 T cells profile among individuals with severe asthma refractory to treatment. Objective: To evaluate the CD4 T lymphocyte profile from individuals with severe asthma according to their response to treatment, relating to their atopy status and age of asthma onset. Methods: We evaluated nineteen individuals with severe asthma refractory to treatment (SAR), 21 with well‐controlled or partly controlled severe asthma (CSA) and 23 with mild‐to‐moderate asthma (MMA). Lymphocytes were obtained from PBMC, and the frequency of expression of different molecules in this population was assessed using the flow cytometry. Results: We observed the frequency of CD4 + IFN‐γ + T cells was higher in atopic individuals with SAR than with CSA. In addition, among the atopic and early‐onset asthma (EOA), the frequency of CD4 + CTLA‐4 + T cells was lower in the SAR group than the CSA group. In relation to non‐atopic and late‐onset asthma (LOA) phenotypes, we noted the frequency of CD4 + FoxP3 + T cells was lower in individuals with SAR than with CSA. We also observed among the LOA patients, the frequency of CD4 + TGF‐β + T cells was decreased in SAR group than the in CSA group. Conclusion and Clinical Relevance: Our data suggest that refractoriness to treatment in asthma is associated with a lower expression of distinct regulatory molecules by CD4 T cells between those who are atopic and have EOA and those who are non‐atopic and have LOA. Thus, these results may contribute to the identification of new regulatory strategies to treat asthma according to their phenotypes.